Technology as A Determinant of Mother's Knowledge About Stunting In Toddlers Aged 1-5 Years Old Tanjung Sari Natar Village Selatan - Syahroni, Arfan; Nugroho, Tri Adi (RADINKA JOURNAL OF HEALTH SCIENCE, 2023)
Stunting refers to a condition when a child experiences impaired growth and development for his age due to malnutrition. Factors that cause stunting can be found during pregnancy or the early stages of child growth. In this study, researchers wanted to find out about the use of technology as a determinant of mothers' knowledge about stunting in toddlers aged 1-5 years. This type of research is quantitative using a cross-sectional study design. The design of this study was chosen to identify the influence of variables on Android mobile phones and growth and development applications on maternal knowledge about stunting aged 1-5 years. The research population was all mothers who had toddlers aged 1-5 years in Tanjung Sari Natar Village, South Lampung. The sample size using the non-probability sampling quota sampling technique is 50 respondents. The test was carried out using the Pearson correlation test, whether ownership of an Android mobile phone and growth and development applications is related to a mother's knowledge about stunting. The results of a significance value > 0.05 (cellphone 0.195, growth and development applications 0.113) mean that there is no significant correlation between owned mobile phones and growth and development applications, with knowledge of stunting.